Motivation to interaction media: The impact of automation trust and self-determination theory on intention to use the new interaction technology in autonomous vehicles - Xie, Yubin; Zhou, Ronggang; Chan, Alan Hoi Shou; Jin, Mingyu; Qu, Miao (Frontiers in Psychology, 2023)
This research investigated the effects of three psychological needs (competence, autonomy, and relatedness) of self-determination theory (SDT) and automation trust on the intention of users to employ new interaction technology brought by autonomous vehicles (AVs), especially interaction mode and virtual image. This study focuses on the discussion from the perspective of psychological motivation theory applied to AV interaction technology. With the use of a structured questionnaire, participants completed self-report measures related to these two interaction technologies; a total of 155 drivers’ responses were analysed. The results indicated that users’ intentions were directly predicted by their perceived competence, autonomy, and relatedness of SDT and automation trust, which jointly explained at least 66% of the variance in behavioural intention. In addition to these results, the contribution of predictive components to behavioural intention is influenced by the type of interaction technology. Relatedness and competence significantly impacted the behavioural intention to use the interaction mode but not the virtual image. These findings are essential in that they support the necessity of distinguishing between types of AV interaction technology when predicting users’ intentions to use.